Reactive oxygen species (ROS) mediated enhanced anti-candidal activity of ZnS-ZnO nanocomposites with low inhibitory concentrations - Suyana, P.; Nishanth Kumar, S.; Madhavan, N.; Dileep Kumar, B.; Nair, Balagopal; Mohamed, A.; Warrier, K.; Hareesh, U. (Royal Society of Chemistry, 2015)
Enhanced antifungal activity against the yeast species Candida albicans, Candida tropicalis and Saccharomyces cerevisiae was displayed by ZnS-ZnO nanocomposites prepared by a simple precipitation technique. The antifungal activity was significantly more in the presence of indoor light than under dark conditions and was a clear confirmation of the inhibitory role of reactive oxygen species (ROS) generated in situ by the photocatalytic nanocomposites. The generation of ROS was further evidenced by flow cytometry results and membrane permeabilisation studies. Time kill assay and growth curve analysis indicated diminished antifungal activity under dark conditions due primarily to Zn2+ efflux in solution. © 2015 The Royal Society of Chemistry.